Evaluation of CBSX Proteins as Regulators of the Chloroplast Thioredoxin System - Murai, Ryota; Okegawa, Yuki; Sato, Nozomi; Motohashi, Ken (Frontiers in Plant Science, 2021)
The chloroplast-localized cystathionine β-synthase X (CBSX) proteins CBSX1 and CBSX2 have been proposed as modulators of thioredoxins (Trxs). In this study, the contribution of CBSX proteins to the redox regulation of thiol enzymes in the chloroplast Trx system was evaluated both in vitro and in vivo. The in vitro biochemical studies evaluated whether CBSX proteins alter the specificities of classical chloroplastic Trx f and Trx m for their target proteins. However, addition of CBSX proteins did not alter the specificities of Trx f and Trx m for disulfide bond reduction of the photosynthesis-related major thiol enzymes, FBPase, SBPase, and NADP-MDH. In vivo analysis showed that CBSX-deficient mutants grew similarly to wild type plants under continuous normal light conditions and that CBSX deficiency did not affect photo-reduction of photosynthesis-related thiol enzymes by Trx system at several light intensities. Although CBSX proteins have been suggested as modulators in the chloroplast Trx system, our results did not support this model, at least in the cases of FBPase, SBPase, and NADP-MDH in leaves. However, fresh weights of the cbsx2 mutants were decreased under short day. Since Trxs regulate many proteins participating in various metabolic reactions in the chloroplast, CBSX proteins may function to regulate other chloroplast Trx target proteins, or serve as modulators in non-photosynthetic plastids of flowers. As a next stage, further investigations are required to understand the modulation of Trx-dependent redox regulation by plastidal CBSX proteins.